2022
DOI: 10.1007/s12032-021-01628-1
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 spike protein inhibits growth of prostate cancer: a potential role of the COVID-19 vaccine killing two birds with one stone

Abstract: To investigate the effects of isolated SARS-CoV-2 spike protein on prostate cancer cell survival. The effects of SARS-CoV-2 spike protein on LNCaP prostate cancer cell survival were assessed using clonogenic cell survival assay, quick cell proliferation assay, and caspase-3 activity kits. RT-PCR and immunohistochemistry were performed to investigate underlying molecular mechanisms. SARS-CoV-2 spike protein was found to inhibit prostate cancer cell proliferation as well as promote apoptosis. Further investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…1B). This is consistent with our previous publication [27]. These results demonstrate that the SP of SARS-CoV-2 negatively affects the proliferation and survival of LNCaP cells.…”
Section: The Time-dependent Effect Of Sars-cov-2 Sp On Lncap and Pc-3...supporting
confidence: 94%
See 3 more Smart Citations
“…1B). This is consistent with our previous publication [27]. These results demonstrate that the SP of SARS-CoV-2 negatively affects the proliferation and survival of LNCaP cells.…”
Section: The Time-dependent Effect Of Sars-cov-2 Sp On Lncap and Pc-3...supporting
confidence: 94%
“…One pro-proliferative gene upregulated through this pathway is CDK4 [35]. This is of particular interest to our lab given that in our recent study CDK4 expression was downregulated in LNCaP cells in the presence of SP, which correlated with suppressed cell proliferation [27]. In this study, we did not test whether the observed inhibitory effects of SP on the growth of LNCaP cells is related to expression levels of the androgen receptor.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The anti-proliferative effect of SARS-CoV-2 spike protein on prostate cancer cells was associated with downregulation of cyclin-dependent kinase 4. The increased apoptosis of prostate cancer cells induced by SARS-CoV-2 spike protein was associated with the upregulation of Fas ligand [7]. We further expanded our study to investigate if SARS-CoV-2 spike protein has any effect on expression of costimulatory molecules.…”
Section: Letter To the Editormentioning
confidence: 93%